Neurogenesis and Increase in Differentiated Neural Cell Survival via Phosphorylation of Akt1 after Fluoxetine Treatment of Stem Cells. (18th August 2013) - Rahmani, Anahita; Kheradmand, Danial; Keyhanvar, Peyman; Shoae-Hassani, Alireza; Darbandi-Azar, Amir
Abstract : Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRI). Its action is possibly through an increase in neural cell survival. The mechanism of improved survival rate of neurons by FLX may relate to the overexpression of some kinases such as Akt protein. Akt1 (a serine/threonine kinase) plays a key role in the modulation of cell proliferation and survival. Our study evaluated the effects of FLX on mesenchymal stem cell (MSC) fate and Akt1 phosphorylation levels in MSCs. Evaluation tests included reverse transcriptase polymerase chain reaction, western blot, and immunocytochemistry assays. Nestin, MAP-2, and β -tubulin were detected after neurogenesis as neural markers. Ten μ M of FLX upregulated phosphorylation of Akt1 protein in induced hEnSC significantly. Also FLX did increase viability of these MSCs. Continuous FLX treatment after neurogenesis elevated the survival rate of differentiated neural cells probably by enhanced induction of Akt1 phosphorylation. This study addresses a novel role of FLX in neurogenesis and differentiated neural cell survival that may contribute to explaining the therapeutic action of fluoxetine in regenerative pharmacology.